Adapting to changes in volcanic behaviour: Formal and informal interactions for enhanced risk management at Tungurahua Volcano, Ecuador. (July 2017) - Armijos, Maria Teresa; Phillips, Jeremy; Wilkinson, Emily; Barclay, Jenni; Hicks, Anna; Palacios, Pablo; Mothes, Patricia; Stone, Jonathan
Highlights: We consider how 'shadow networks' help communities adapt to environmental change and uncertainty. The findings suggest that 'shadow networks' have facilitated improvements in hazard monitoring, communication, and in evacuation processes. There have been improvements in collective responses to volcanic risk, allowing people to maintain their livelihoods. A step change may now be required to anticipate and respond better to rapid-onset volcanic activity. Abstract: This paper provides an example of how communities can adapt to extreme forms of environmental change and uncertainty over the longer term. We analyse the interactions between scientists, communities and risk managers and examine the interpretation and communication of uncertain scientific information during a long-lived volcanic eruption in Tungurahua, Ecuador. This is complemented with a detailed study of the eruptions of 2006 and 2014, which exemplifies the complexity of interactions during periods of heightened volcanic activity. Our study describes how a 'shadow network' has developed outside of, but in interaction with, the formal risk management institutions in Ecuador, improving decision-making in response to heightened volcanic activity. The findings suggest that the interactions have facilitated important adaptations in the scientific advisory response during eruptions (near-real-time interpretation of the volcanic hazards), in hazard communication, and in the evacuation processes. Improved communication between stakeholders and the establishment of thresholds for evacuations have created an effective voluntary evacuation system unique to Tungurahua, allowing people to continue to maintain their livelihoods during heightened volcanic activity and associated periods of uncertainty. Understanding how shadow networks act to minimise the negative consequences of volcanic activity provides valuable insights for increasing societal resilience to other types of hazards.